Tanggung Jawab Pemerintah Desa dalam Mendorong Kinerja Badan Usaha Milik Desa di Desa Kualin dan Desa Oni Kecamatan Kualin, Kabupaten Timor Tengah Selatan Ditinjau dari Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Vicky Icshin Anjaibar Penuam; David Y. Meyners; Herinimus Ratu Udju (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the responsibilities of the village government in encouraging the performance of Village-Owned Enterprises in Kualin Village and Oni Village, Kualin Sub-district, South Central Timor District in terms of Law Number 6 of 2014 concerning Villages. The method used in this research is empirical legal research, namely examining the responsibilities of the Village Government according to Law Number 6 of 2014 concerning Villages implemented in Kualin District, South Central Timor Regency by seeing how the law is applied in community life both through interviews and observations. The research locations are Kualin village and Oni village. The type of data used in this research consists of primary and secondary data. Based on the research results obtained that the responsibility of the Village Government in encouraging the performance of Village-Owned Enterprises in Kualin village and Oni village, namely responsibility is in the form of village government services (a). Village Service Standards such as general public services. (b) BUMDes management. Factors that hinder the responsibility of the village government in Kualin Village and Oni Village in Kualin Sub-district, South Central Timor Regency are Human Resources such as lack of awareness of the importance of education. Facilities and infrastructure.